Current Opinions and Practices of Bariatric Surgery in Adolescents: A Survey among Pediatric Surgeons - Roebroek, Yvonne G. M.; Pruijssers, Suzanne R.; Bouvy, Nicole D.; van Heurn, Ernest L. W. E. (European Journal of Pediatric Surgery, 2020)
Introduction Bariatric surgery is performed at increasing rate in severely obese adolescents who do not respond to conservative treatment. In the United States, this treatment is generally accepted, yet in Europe, surgeons are more reluctant because of concerns regarding safety and (long-term) efficacy. We evaluated in which (European) countries bariatric surgery is allowed and performed, and the opinion of the members of the European Paediatric Surgeons' Association (EUPSA) regarding bariatric surgery in adolescents.Materials and Methods Information was obtained with an online questionnaire sent to all EUPSA members.Results A total of 108 pediatric surgeons (PSs) from 33 countries (of which 25 European) completed the survey. Sixty-two PSs (57.4%) from 22 countries stated that bariatric surgery in adolescents was allowed in their country. In only 14 countries, the costs were (partially) covered by health care insurances. Overall, 65.7% of the surgeons (n = 71) believed bariatric surgery may offer a valuable contribution to obtain substantial long-term weight loss in severely obese adolescents. Fifty-one (47.2%) reported that these procedures should be performed by a combination of a bariatric and a PS, while 20 (18.5%) and 16 (14.8%) preferred that these procedures should be performed solely by a PS or bariatric surgeon, respectively.Conclusion Although allowed in most European countries, bariatric surgery in adolescents is only practiced on a small scale, and the treatment is often excluded from regular health care reimbursement. The majority of PSs acknowledge the value of bariatric surgery, which should be performed by a combination of PS and bariatric surgeon.
Keywords: pediatrics; severe obesity; bariatric surgery